Isolation and in vitro antimalarial activity of hexane extract from Thai Picrasma javanica B1 stembark. - Saiin C. (2014)
The in vitro antimalarial activities against Plasmodium falciparum K1 of four extracts from the stembark of Picrasma javanica B1; ie water, methanol, chloroform and hexane extracts were studied using a modification of the [3H]hypoxanthine incorporation method. It was found that the hexane extract showed in vitro antimalarial activity with IC50 of 3.3 microg/ml. The extract was further fractionated using quick column chromatography, resulting in ten fractions. Fraction V was the most effective against P. falciparum K1 with IC50 of 4.4 microg/ml. Further isolation of fraction V using a column chromatographic technique provided six fractions. According to 1H- and 13C-NMR spectra, it could be concluded that the major compound in fraction V-3 was beta-sitosterol. Unfortunately, the antimalarial activity of beta-sitosterol could not be determined because of its low solubility in DMSO. However, fractions V-2 and V-4 still showed in vitro antimalarial activities with IC50 of 2.8 and 3.4 microg/ml, respectively. The further fractionation of these two active fractions could lead to promising candidates as antimalarial agents.